MODEL PEMBELAJARAN DISKOVERI SEBAGAI STRATEGI PEMBELAJARAN BAHASA ARAB - Mahyudin, Erta (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2014)
Teaching strategy is very important in Arabic Classroom. It covers design and dimension. One of the model in the instructional design is discovery learning. In teaching Arabic language discovery model called guided discovery. In this model the exposure of linguistic material is given firstly, and followed by the rule of language. DOI: 10.15408/a.v1i2.1139